PENINGKATAN KINERJA MANAJEMEN PENGENDALIAN ASET TETAP KABUPATEN PURBALINGGA - Rokhmadi, Faqikh Andri; Baga, Lukman Mohammad; Ristiyanto, Nirwan (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2018)
ABSTRACTThe Government of Purbalingga Regency during the years 2011-2015 have received qualified opinion (WDP) from The Supreme Audit Agency (BPK) on the results of the audit of its financial statements. They are many problems in the presentation of fixed assets in their financial statements. This study aims to: (1) to analyze the existence of administration system of fixed asset in Purbalingga regency; (2) to analyze the weaknesses of administration system of fixed asset in Purbalingga regency; and (3) to formulate recommendation for improvement of administration system of fixed asset in Purbalingga regency. Formulation of strategy is done using SWOT analysis and strategic architecture. Then, the proposed strategies for improving the fixed asset administration system are the completion of fixed asset issues, improvement of inter-institution cooperation in asset management, improvement of human resources competence in asset management, improvement of compensation and rewards on the human resources performance in asset management, improvement of inters-institution coordination in asset management, implementation of action plan through escorting the follow-up audit findings by the Inspectorate, implementation of an action plan through census and reconciliation of asset data on a regular basis, and the implementation of an action plan through enhancement of the role of the Inspectorate in safeguarding asset.Keywords : Financial Statement, Fixed Asset, Strategic Architecture, SWOT AnalysisABSTRAKPemerintah Kabupaten Purbalingga selama tahun 2011 sampai dengan tahun 2015 mendapatkan opini Wajar Dengan Pengecualian (WDP) dari Badan Pemeriksa Keuangan (BPK) atas hasil audit laporan keuangannya. Terdapat berbagai permasalahan pada penyajian aset tetap dalam laporan keuangan. Penelitian ini bertujuan untuk: (1) menganalisis tinjauan keberadaan sistem kegiatan penatausahaan aset tetap Kabupaten Purbalingga; (2) menganalisis berbagai kelemahan sistem kegiatan penatausahaan aset tetap Kabupaten Purbalingga; dan (3) merumuskan rekomendasi perbaikan sistem kegiatan penatausahaan aset tetap Kabupaten Purbalingga. Perumusan strategi dilakukan dengan menggunakan analisis SWOT dan arsitektur strategi. Selanjutnya, strategi yang diusulkan dalam upaya perbaikan sistem kegiatan penatausahaan aset adalah penuntasan permasalahan aset tetap, peningkatan kerjasama antar lembaga dalam pengelolaan aset, peningkatan kompetensi SDM pengelola aset, perbaikan kompensasi dan penghargaan atas prestasi kerja dari SDM pengelola aset, peningkatan koordinasi antar lembaga dalam pengelolaan aset, pelaksanaan action plan melalui pengawalan pelaksanaan tindak lanjut temuan audit oleh Inspektorat, pelaksanaan action plan melalui sensus dan rekonsiliasi data aset secara rutin, pelaksanaan action plan melalui peningkatan peranan Inspektorat dalam pengamanan aset.Kata Kunci: Laporan Keuangan, Aset Tetap, Arsitektur Strategi, Analisis SWOT